2006
DOI: 10.1079/bjn20051680
|View full text |Cite
|
Sign up to set email alerts
|

Trans-11–18: 1 is effectively δ9-desaturated compared withTrans-12–18: 1 in humans

Abstract: The aim of this human intervention study was to evaluate the D9-desaturation of trans-11-18 : 1 (trans-vaccenic acid; tVA) to cis-9,trans-11-18 : 2 (c9,t11 conjugated linoleic acid; CLA) and of trans-12-18 : 1 (t12) to cis-9,trans-12-18 : 2 after a short-term (7 d) and a long-term (42 d) supplementation period. The conversion rates of both trans-18 : 1 isomers were estimated by lipid analysis of serum and red blood cell membranes (RBCM). Subjects started with a 2-week adaptation period without supplements. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 59 publications
5
75
2
1
Order By: Relevance
“…In the present study, the CLA level reached 20 mg/100 g of meat, which is in line with those reported in other studies on suckling lambs (Serra et al, 2009). Assuming a 20% to 25% conversion rate in the human body of vaccenic acid to CLA, the measured vaccenic acid level would provide 5 mg of CLA (Kuhnt et al, 2006). By adding the CLA and the vaccenic acid converted into CLA, lamb meat produced using this feeding strategy would provide approximately 25 mg of CLA/100 g of meat.…”
Section: Milk Fatty Acid Compositionsupporting
confidence: 92%
“…In the present study, the CLA level reached 20 mg/100 g of meat, which is in line with those reported in other studies on suckling lambs (Serra et al, 2009). Assuming a 20% to 25% conversion rate in the human body of vaccenic acid to CLA, the measured vaccenic acid level would provide 5 mg of CLA (Kuhnt et al, 2006). By adding the CLA and the vaccenic acid converted into CLA, lamb meat produced using this feeding strategy would provide approximately 25 mg of CLA/100 g of meat.…”
Section: Milk Fatty Acid Compositionsupporting
confidence: 92%
“…The fatty acid (FA) composition of in vitro fermented nut samples (FP) was analyzed via GC (GC-17A V3 equipped with an autosampler AOC-5000 and a flame ionization detector; Shimadzu) as described by Kuhnt et al [18]. Therefore, lipids were extracted from 0.5 g FP as described by Folch et al [26] using a mixture of chloroform/methanol/NaCl (v/v/v 2:1:1) and transesterified with 0.5 N methanolic sodium hydroxide (100 °C, 10 min) and 1 mL methanolic BF3 solution (10 %, w:w; 100 °C, 5 min).…”
Section: Analysis Of the Fatty Acid Composition In Fermentation Pelletsmentioning
confidence: 99%
“…In contrast, natural occurring tFA such as C18:1t11 (tVA, trans vaccenic acid) and conjugated linoleic acids (CLA) might be associated with positive health effects as reviewed by Gebauer et al [14]. These ruminant tFA are intermediates in the microbial biohydrogenation of PUFA during fermentation by the rumen intestinal microbiota resulting generally in a low t9/t11 index in dairy products (<1) [18]. CLA are isomers of LA with conjugated double bonds in trans and cis configurations which are converted, for example, from LA via the biohydrogenation process.…”
mentioning
confidence: 94%
“…Throughout biohydrogenation rumenic acid is formed from linoleic acid in the rumen by anaerobic bacteria (such as Butyrivibrio fibrisolvens), with vaccenic acid (t11C18:1) as intermediates. The vaccenic acid is converted to rumenic acid by Δ 9 -desaturase in mammary gland and also in some human tissues (Kuhnt et al, 2006). Some authors reported that diet can exert influence on rumenic acid concentration in milk, such as high protein level (Czauderna et al, 2010) and supplemental sunflower fat (Martínez et al, 2012).…”
Section: Control Diet Experimental Dietmentioning
confidence: 99%